The Effect of Return on Assets, Return on Equity, Debt to Equity Ratio, and Current Ratio on Stock Returns in Companies Listed in the LQ 45 Index on the Indonesia Stock Exchange 2017 - 2019 - Desi Nopitasari Hadameon Nainggolan; Widya Andravana Hia; Lorenza Kristi Mona; Ferdinand Napitupulu (Jurnal Mantik, 2021)
The purpose of this study is to observe the effect of ROA, ROE, DER, and CR on stock returns in companies listed in the LQ 45 index on the IDX. Observations used the T test, F test, and used quantitative descriptive. Many populations were used for research, namely 45 companies in the 2017-2018 period and purposive sampling was carried out on this population to obtain samples. There are 31 companies obtained as samples. The data analysis technique used for this study is the multiple linear regression analysis technique. In this study, it shows partially only DER which has a positive and significant effect on stock returns and simultaneously the four variables used have a positive and significant effect on stock returns. In the determination coefficient test, it can be seen that the adjust r square (R2) number is 0,